Broadly neutralizing antibodies to SARS-CoV-2 and other human coronaviruses - Chen, Yanjia; Zhao, Xiaoyu; Zhou, Hao; Zhu, Huanzhang; Jiang, Shibo; Wang, Pengfei (Nature reviews. Immunology, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a recently emerged pathogenic human coronavirus that belongs to the sarbecovirus lineage of the genus Betacoronavirus. The ancestor strain has evolved into a number of variants of concern, with the Omicron variant of concern now having many distinct sublineages. The ongoing COVID-19 pandemic caused by SARS-CoV-2 has caused serious damage to public health and the global economy, and one strategy to combat COVID-19 has been the development of broadly neutralizing antibodies for prophylactic and therapeutic use. Many are in preclinical and clinical development, and a few have been approved for emergency use. Here we summarize neutralizing antibodies that target four key regions within the SARS-CoV-2 spike (S) protein, namely the N-terminal domain and the receptor-binding domain in the S1 subunit, and the stem helix region and the fusion peptide region in the S2 subunit. Understanding the characteristics of these broadly neutralizing antibodies will accelerate the development of new antibody therapeutics and provide guidance for the rational design of next-generation vaccines. The ancestral strain of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has evolved into a number of variants of concern. In this Review, Wang and colleagues discuss progress in the development and characterization of broadly neutralizing antibodies to SARS-CoV-2, which may lead to new antibody therapeutics and inform the design of next-generation vaccines.